Tobacco control in the European Union - Bogdanovica, Ilze (2012)
Smoking is the leading avoidable cause of mortality and serious disability worldwide. The prevalence of smoking varies greatly between the 27 European Union (EU) Member States as does the implementation of tobacco control policies. The main aims of this thesis were to investigate the extent of the variation between and the reliability of measures of smoking prevalence, the relation between prevalence and tobacco control policy implementation, the country characteristics associated with policy implementation, and a detailed analysis of the association between cigarette prices and smoking prevalence.